IsiA Is Required for the Formation of Photosystem I Supercomplexes and for Efficient State Transition in Synechocystis PCC 6803 - Wang, Qiang (Public Library of Science, 2010)
Iron deficiency and other stress conditions strongly impact photosynthetic apparatus in photosynthetic organisms. Two novel chlorophyll (Chl)-containing supercomplexes (F4 and F5) in addition to the photosystem (PS) I trimers (F3) were observed by sucrose gradient ultracentrifugation in Synechocystis PCC 6803 under extensive iron starvation. 77K fluorescence and Western blot analyses of these supercomplexes revealed that they all contained IsiA. The F4 was identified as an IsiA-PSI-PSII supercomplex, while the F5 was assigned as an IsiA-PSI supercomplex. Deletion of isiA resulted in diminishing the PSI trimers (including the PSI trimers in iron-replete cells) and the two novel PSI supercomplexes (F4 and F5), and a significant reduction in the saturated whole-chain electron transport rate. However, the maximum PSII activities remained at levels similar to those of the wild type under various light conditions. The isiA(-) mutant was defective in state transition and sensitive to high light. The sensitivity of the isiA(-) mutant to high light was correlated with a higher level of membrane peroxidation. These results demonstrated that IsiA is required for the formation of PSI trimers and other higher complexes, and that IsiA is critical for efficient state transition.